The Hubungan antara Kadar Trigliserida dengan Kadar HbA1c Pada Pasien DM Tipe II - Ahmad Hafid; Suharmanto Suharmanto (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Background; Diabetes Mellitus (DM) is a chronic disease characterized by hyperglycemia is caused by a lack of insulin production or ineffectiveness of the insulin. The higher the level of sugar in the blood will cause the accumulation of abdominal adipose tissue which is more easily lipolytic, resulting in an increase in triglyceride levels. Purpose: This study aims to describe the relationship between HbA1c and triglyceride levels in patients with type 2 diabetes. Method: The method used in this study is retrospective observational analytic which uses a cross-sectional approach, using secondary data. The number of respondents was 1,360 DM patients who visited health services in Lampung Province in 2020. Research Result: the analysis between triglyceride levels and HbA1c levels showed the result of p=0.000, Because the value of p=0.000 <0.05, it can be stated that Ha is accepted and Ho rejected or there is a significant relationship between triglyceride levels and HbA1c levels. Conclusion: showed that there was a positive relationship between triglyceride levels and HbA1c levels according to the National Glycohemoglobin Standardization Program (NGSP)